Antibodies from plants for bionanomaterials. (27th March 2017) - Edgue, Gueven; Twyman, Richard M; Beiss, Veronique; Fischer, Rainer; Sack, Markus
Abstract : Antibodies are produced as part of the vertebrate adaptive immune response and are not naturally made by plants. However, antibody DNA sequences can be introduced into plants, and together with laboratory technologies that allow the design of antibodies recognizing any conceivable molecular structure, plants can be used as 'green factories' to produce any antibody at all. The advent of plant‐based transient expression systems in particular allows the rapid, convenient, and safe production of antibodies, ranging from laboratory‐scale expression to industrial‐scale manufacturing. The key features of plant‐based production include safety, speed, low cost, and convenience, allowing newcomers to rapidly master the technology and use it to its full advantage. Manufacturing in plants has recently achieved significant milestones and offers more than just an alternative to established microbial and mammalian cell platforms. The use of plants for product development in particular offers the power and flexibility to easily coexpress many different genes, allowing the plug‐and‐play construction of novel bionanomaterials, perfectly complementing existing approaches based on plant virus‐like particles. As well as producing single antibodies for applications in medicine, agriculture, and industry, plants can be used to produce antibody‐based supramolecular structures and scaffolds as a new generation of green bionanomaterials that promise a bright future based on clean and renewable nanotechnology applications. WIREs Nanomed Nanobiotechnol 2017, 9:e1462. doi: 10.1002/wnan.1462 This article is categorized under: Therapeutic Approaches and Drug Discovery > Emerging Technologies Diagnostic Tools > In Vivo Nanodiagnostics and Imaging Biology-Inspired Nanomaterials > Protein and Virus-Based Structures Abstract : Plants are ideal for making antibodies and other recombinant proteins. The agroinfiltration system is particularly useful due to its speed and scalability and represents a powerful tool for generating plant antibodies to analyse and construct nanomaterials. Many recombinant genes can be coexpressed efficiently and this greatly supports synthetic biology approaches and allows for the combination with, e.g., plant virus‐like particles to assemble antibody‐based supramolecular structures and scaffolds.